The level of Facebook addiction among university students-A field study on a sample of university students at The University Center of Si El Hawas Barika - Khediri, Mohamed; Yahiaoui, Warda (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
The current study aimed to Identifying the level of Facebook addiction among university students, also examined whether there were differences among them in level of Facebook addiction due to gender variable, in order to achieve the objective of the study the descriptive approach was relied, and the Bergen Facebook addiction scale prepared by Cecilie Schou Andreassen with his colleagues at The University of Bergen-Norway (2012) was application on a prospective sample of 30 students to verify Its psychometric properties, its reliability was confirmed by calculating Cronbach’s alpha coefficient, its validity was confirmed by calculating the construct, the final version of the tool consisted of 18 statements distributed over six dimensions: prominence, endurance, mood, relapse, withdrawal, conflict, the tool was applied to the main research sample (39), The following statistical methods were used: Pearson correlation coefficient, T-test for differences, arithmetic mean, standard deviation, and then we reached the following results: the level of Facebook addiction among university students is average, there are not statistically significant differences in addiction to Facebook among university students due to the gender variable, based on the study’s results we have recommend some suggestions aimed at reducing university students addiction to Facebook, as well as conducting in depth studies on the phenomenon of Facebook addiction, Implementing therapeutic and programs that have proven effective.